Spontaneous regression of a giant uterine leiomyoma after delivery: a case report and literature review - Lifang Zhu-ge; Qiaoli Bei; Weiping Pan; Xiaojun Ni (BMC, 2024)
Abstract Background Uterine leiomyomas are hormone-dependent benign tumors and often begin to shrink after menopause due to the reduction in ovarian steroids. The influence of pregnancy on uterine leiomyomas size remains unclear. Here, we present a case of spontaneous regression of a giant uterine leiomyoma after delivery. Case presentation A 40-year-old woman presented with multiple uterine leiomyomas, one of which is a giant uterine leiomyomas (approximately 8 cm in diameter) that gradually shrinked after delivery. At over two months postpartum, the large myometrial leiomyoma had transformed into a submucosal leiomyoma, and over 3 years postpartum, both the submucosal leiomyoma and multiple intramural leiomyomas completely regressed. Conclusion Spontaneous regression of a giant uterine leiomyom is rare after delivery. Considering uterine leiomyoma regression until over 3 year postpartum,we need to observe the regression of uterine fibroid for a longer time postpartum in the absence of fibroid related complications. In addition, it will provide new insights for treatment options of uterine leiomyomas in the future.